The Role of Non-Coding RNAs in Autophagy During Carcinogenesis - de la Cruz-Ojeda, Patricia; Flores-Campos, Rocío; Navarro-Villarán, Elena; Muntané, Jordi (Frontiers in Cell and Developmental Biology, 2022)
Macroautophagy (autophagy herein) is a cellular stress response and a survival pathway involved in self-renewal and quality control processes to maintain cellular homeostasis. The alteration of autophagy has been implicated in numerous diseases such as cancer where it plays a dual role. Autophagy serves as a tumor suppressor in the early phases of cancer formation with the restoration of homeostasis and eliminating cellular altered constituents, yet in later phases, autophagy may support and/or facilitate tumor growth, metastasis and may contribute to treatment resistance. Key components of autophagy interact with either pro- and anti-apoptotic factors regulating the proximity of tumor cells to apoptotic cliff promoting cell survival. Autophagy is regulated by key cell signaling pathways such as Akt (protein kinase B, PKB), mammalian target of rapamycin (mTOR) and AMP-activated protein kinase (AMPK) involved in cell survival and metabolism. The expression of critical members of upstream cell signaling, as well as those directly involved in the autophagic, and apoptotic machineries are regulated by microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). Consequently, non-coding RNAs play a relevant role in carcinogenesis and treatment response in cancer. The review is an update of the current knowledge in the regulation by miRNA and lncRNA of the autophagic components and their functional impact to provide an integrated and comprehensive regulatory network of autophagy in cancer.